Online High School Community Health Worker Curriculum: Key Strategies of Transforming, Engagement, and Implementation - Zheng, Jinjie; Williams-Livingston, Arletha; Danavall, N'Dieye; Ervin, Christopher; McCray, Gail (Frontiers in Public Health, 2021)
Background: Ample research evidence has demonstrated that Community Health Worker (CHW) programs are a cost-effective, culturally integrated, and impactful way to improve community health. Although most existing CHW programs recruit adults as CHWs, high school students, with their intellectual readiness and intimate community knowledge, also have great potential to be engaged as CHWs that impact community health. With this potential in mind, the High School Community Health Worker Curriculum (HSCHW), for face-to-face training, was created in 2016 at Morehouse School of Medicine (MSM) as an innovative solution to improve community health in underserved, urban neighborhoods. Sixteen Metro Atlanta high school students participated in the program's first cohort. The face-to-face HSCHW training program received very positive feedback from the students and community partners involved. Additionally, during the inaugural training, the program received more than 150 nationwide inquiries about an opportunity to either participate in the program or replicate its curriculum. Hence, in 2018, a corresponding online curriculum was created to meet these needs. The online HSCHW curriculum covers the roles and competencies described in the CHW Core Consensus (C3) Project and focuses on developing high school students' critical thinking, decision-making, and communication skills. As of February 2021, 346 high school community health workers have participated in this online curriculum. Purpose: This paper reports on the research study of the critical processes and strategies of transforming, engaging, and implementing the online HSCHW curriculum. Method: The project team conducted the research study to identify the key strategies to transform the face-to-face HSCHW curriculum, the engagement strategies embedded in the online curriculum's content development, and, ultimately, the curriculum's outcomes. Altogether, this mixed-method study analyzed and reported on the learning outcomes of 265 students', in tandem with 17 high school students' focused-group interviews and responses to online surveys. Results: The results showed that integrating instructional design processes is critical for the online curriculum's success. “Interestingness,” the latent concept embedded in the online HSCHW curriculum, engages high school students in learning about complex CHW skills, through digital content and activities. Furthermore, the successful implementation of the program and its student learning outcomes was assured by integrating the online curriculum with local schools and community resources, training the local community and school “trainers” to facilitate the curriculum online, and providing ongoing coaching support from the program team. Impacts: This paper provides a research report on the key strategies and processes of creating and implementing an online CHW curriculum for high school students. Its findings will inform future endeavors to develop an online CHW curriculum for lifelong learners and increase training effectiveness. The online HSCHW curriculum increases the national capacity of community health workers, whose work will increase community engagement and health equity. The curriculum also empowers high school students to acquire health knowledge that can bridge the educational gap between health knowledge acquisition and health knowledge application. Additionally, the online HSCHW curriculum presents a concrete example of leveraging digital platforms to teach complex public health competencies to young adults who can positively impact community health.